Composite films based on salicylic acid-layered zinc hydroxide and polyvinyl alcohol: Preparation, characterization, properties and potential applications - Ruiz Madronero, Christhy; et al. (Polymer Testing, 2021)
Composite films of Polyvinyl alcohol (PVA) and hybrid materials based on salicylic acid –layered zinc hydroxide acetate (ZHA-SA) using zinc hydroxide acetate (ZHA) as host matrix were obtained by the casting method. The resulting composite films were characterized by FT-IR, X-ray diffraction, scanning electron microscopy (SEM) and atomic force microscopy (AFM) evidencing the incorporation of the layered materials in PVA matrix with relatively smooth and orderly surfaces. A significant reduction in the crystallinity of neat PVA film and a slight increase in transport coefficients of oxygen through the composite films have been observed. This behavior has been attributed to a high compatibility and adhesion between the fillers and polymeric matrix. Evaluation of the mechanical properties, in terms of stress, revealed that a low content of fillers (1.0 wt %) were able to increase the response of PVA composites by 63% with the addition of ZHA, and 45% with ZHA-SA. The results demonstrated the potential application of ZHA and ZHA-derived hybrid material in the preparation of multi-functional polymer composites to be used in packaging food system
Keywords: Hybrid material; Salicylic acid; Layered zinc hydroxide acetate; Poly(vinyl) alcohol Composite films; Reinforcement effect; Stress